Experimental and Analytical Study on Mechanical Properties of High Rock Temperature Diversion Tunnel - Xianchun Yao; Ning Li; Kecheng Wan; Gao Lv; Mingming He (Advances in Civil Engineering)
The high temperature of rock used in different working conditions has a significant effect on the deformation characteristics and the mechanics of tunnel lining support structure. A test using a laboratory model is designed to study the quantitative relationship between the temperature difference and the support force. Through the laboratory model test, the strain and stress variation characteristics of the supporting structure of a water diversion tunnel under different surrounding rock temperatures and different water temperatures were simulated. The variation characteristics of the supporting structure under various working conditions, such as a different initial temperature field, different crossing water temperature of the diversion tunnel during runtime, and repairing period after the water is emptied, were analyzed. The relationship between the high-temperature difference between the inner and outer walls of the tunnel lining support structure and the internal temperature stress of the supporting structure was obtained and compared with the results from numerical experiments. The test results showed that a high circumferential tensile stress is created in the support structure of the high-temperature diversion tunnel due to the temperature difference between the inner and outer walls of the support structure caused by water going through the high-temperature diversion tunnel. The radial compressive stress increases by 45–50%, and the circumferential tensile stress increases by 40–60%. The results provide references for the design of the support structure in a high-temperature tunnel.